Description of two new species of the genus Atlanticus from Southern China and their songs (Orthoptera: Tettigoniidae; Tettigoniinae) - Cheng, Kun; Wang, Xue-Song; Liu, Chun-Xiang; Wu, Chao (Zootaxa, 2016)
Two new species Atlanticus (Sinpacificus) jiangyei sp. n. and Atlanticus (Sinpacificus) helleri sp. n. are described, based on morphology and male calling songs. Based on the morphological characters, the closest relative of Atlanticus (Sinpacificus) jiangyei sp. n. and that of Atlanticus (Sinpacificus) helleri sp. n. are separately assumed to be Atlanticus (Sinpacificus) hangfui Liu, and Atlanticus (Sinpacificus) kiangsui Tinkham. Discussion about characteristics of Atlanticus species is also provided.